2015
DOI: 10.5430/jnep.v5n9p78
|View full text |Cite
|
Sign up to set email alerts
|

High fidelity simulator experience for enhancing communication effectiveness: Applications to quality and safety education for nurses

Abstract: The United States Joint Commission identified miscommunication as the main cause of unexpected injuries and mortality not related to the patient's medical condition. One strategy for improving information transfer and inter-professional communication is the Situation-Background-Assessment-Recommendation (SBAR) communication model. The purpose of this study was to test the effects of exposure to a real time high fidelity simulation experience. A quasi-experimental design, consisting of one treatment group was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[21] Another study found nursing learners' exposure to SBAR during a high-fidelity simulation experience improved their communication skills and competence in patient care and safety according to the Quality and Safety Education for Nurses (QSEN)-based rubric assessment. [22,23] 2. METHOD…”
Section: Literature Reviewmentioning
confidence: 99%
“…[21] Another study found nursing learners' exposure to SBAR during a high-fidelity simulation experience improved their communication skills and competence in patient care and safety according to the Quality and Safety Education for Nurses (QSEN)-based rubric assessment. [22,23] 2. METHOD…”
Section: Literature Reviewmentioning
confidence: 99%